Cdc42 regulates cytokine expression and trafficking in bronchial epithelial cells - Shouib, Rowayna; Eitzen, Gary (Frontiers in Immunology, 2022)
Airway epithelial cells can respond to incoming pathogens, allergens and stimulants through the secretion of cytokines and chemokines. These pro-inflammatory mediators activate inflammatory signaling cascades that allow a robust immune response to be mounted. However, uncontrolled production and release of cytokines and chemokines can result in chronic inflammation and appears to be an underlying mechanism for the pathogenesis of pulmonary disorders such as asthma and COPD. The Rho GTPase, Cdc42, is an important signaling molecule that we hypothesize can regulate cytokine production and release from epithelial cells. We treated BEAS-2B lung epithelial cells with a set of stimulants to activate inflammatory pathways and cytokine release. The production, trafficking and secretion of cytokines were assessed when Cdc42 was pharmacologically inhibited with ML141 drug or silenced with lentiviral-mediated shRNA knockdown. We found that Cdc42 inhibition with ML141 differentially affected gene expression of a subset of cytokines; transcription of IL-6 and IL-8 were increased while MCP-1 was decreased. However, Cdc42 inhibition or depletion disrupted IL-8 trafficking and reduced its secretion even though transcription was increased. Cytokines transiting through the Golgi were particularly affected by Cdc42 disruption. Our results define a role for Cdc42 in the regulation of cytokine production and release in airway epithelial cells. This underscores the role of Cdc42 in coupling receptor activation to downstream gene expression and also as a regulator of cytokine secretory pathways.